Online survey knowledge, attitude and practice on food safety amongst food truck handlers in Shah Alam, Selangor / Mazqhairea Azman and Mohd Izwan Masngut - Azman, Mazqhairea; Masngut, Mohd Izwan (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
In this cross-sectional study, 130 respondents from food truck handlers had answered questionnaires distributed through a social network; Whatsapp Group. This study achieved a good score for Knowledge, Attitude and Practices (KAP) which indicates it is satisfactory level among food truck handlers in Shah Alam. The findings of this study may help in planning health intervention programs for food handlers to improve of knowledge, attitude and practice towards food-borne disease and food safety. Educational training and creating motivation to promote knowledge and turning it into practice seem necessary.